Comprehensive analysis of cancer and non-cancer mortality in patients with bone metastases: A population-based study - Xia Yan; Hongyu Liu; Xueqi Bai; Jin Xu; Xiaojun Lou; Lai Wang (Journal of Bone Oncology)
Purpose: To characterize causes of death in patients with bone metastases and to support data-driven approaches to survivorship planning and clinical decision-making in this population. Methods: Using data from the SEER registry (2010–2021), we identified 186,404 patients with newly diagnosed bone metastases. Causes of death were classified as related to the cancer-specific, non-cancer, or subsequent cancer. Standardized mortality ratios (SMRs) were calculated to assess excess non-cancer mortality relative to the general population. Results: During follow-up, 133,393 patients (71.5 %) died from the primary cancer, 11,062 (5.9 %) from non-cancer causes, and 929 (0.5 %) from other malignancies. Although cancer remained the predominant cause of death, non-cancer mortality increased over time (from 6.3 % in 2010 to 9.5 % in 2021). Cardiovascular disease, COPD, and cerebrovascular events were the most common non-cancer causes. The greatest excess mortality was observed for HIV-related infection conditions (SMR: 13.24), septicemia (10.60), suicide (6.68), and pneumonia/influenza (6.04). Conclusion: Non-cancer mortality is an increasingly important contributor to death among patients with bone metastases, underscoring the need for targeted prevention strategies for infections, cardiovascular disease, and other avoidable causes in this vulnerable population.